Extracellular vesicles-derived extracellular RNA in bladder cancer: current progress and future prospects - Jinbang Chen; Xin Yang; Zihan Hao; Hongqian Guo; Ying Sun; Rong Yang (Therapeutic Advances in Medical Oncology)
Bladder cancer (BCa), ranked as the 10th most common malignancy worldwide, presents significant challenges due to its high recurrence rates and clinical heterogeneity. The current standard diagnostic methods, cystoscopy and urine cytology, demonstrate limited sensitivity, particularly for low-grade tumors, highlighting the urgent need for minimally invasive biomarkers. Extracellular vesicles (EVs), membrane-bound nanoparticles that carry extracellular RNA (exRNA), have emerged as critical players in BCa diagnostics and therapeutics. Recent advancements show that EVs-exRNA facilitates early detection, dynamic monitoring of disease progression, and prognosis prediction. EVs-exRNA, as promising biomarkers, have made substantial progress in BCa research. In this review, we examine the role of EVs-exRNA in BCa, investigate its diagnostic and prognostic value and discuss the challenges and future directions for its clinical application, aiming to provide new insights for future research in this field.